Brand Image and Memorable Culinary Experience as Determinants of Repurchase Intention: A Case Study of Uma Oma Café Jakarta - Nurrizka Putri Ayuningtias; Ramon Hurdawaty (International Journal of Travel, Hospitality and Events, 2026)
This study examines the impact of brand image and memorable culinary experiences on customers’ repurchase intention at Uma Oma Cafe. A quantitative research approach was employed, using a survey of 100 respondents who had visited the café. Data were collected through structured questionnaires and analyzed using multiple linear regression. Data analysis used SPSS 24 software. The research results indicate that both brand image and memorable culinary experiences have a positive and significant effect on repurchase intention (Sig = 0.000; F = 19.855). The coefficient of determination shows that 29% of variables contribute to explaining a portion of customers’ repurchase behavior, while the remaining variance is influenced by other factors not examined in this study. These findings highlight the importance of maintaining a strong brand image and delivering memorable dining experiences as strategic efforts to enhance customer loyalty in the culinary industry. This study contributes to the literature by providing empirical evidence on the combined role of brand image and experiential factors in shaping repurchase intention.